Recent America : a thematic study : kolegij dr.sc. Marka Metzlera Sawina, PDS književnosti, izvedbenih umjetnosti, filma i kulture, akad. god. 2008/09 : čitanka - Salinger, J. D. (2008)
World War II radically shook most European nations’ infrastructures and shattered the power of the colonial empires that had largely dominated the globe since the 18th century. Though America did suffer losses during WWII, they were minor in comparison, and it thus emerged from the war as the new world power. Its industries out produced the rest of the world combined, its infrastructure and scholarly institutions were stronger than ever, its population was rapidly expanding, and it alone possessed the Atomic Bomb. With this new found power, America began a tumultuous half-century that was marked by massive struggles for civil and human rights, aggressive and ruthless business practices, odd and exciting cultural innovations, drastic shifts in social structures, and an astounding consumption spree (some sources suggest that Americans consumed more between 1950 and 2000 than every human that had ever existed before 1950).